Peningkatan Pemahaman Pola Asuh Positif Melalui Seminar Parenting bagi Wali Murid PAUD dan TK Muslimat Mazroatul Ulum 02: Seminar Parenting - Gholiyah Ayu Rosyadah; Herlina Khudhriyah; Asifah, Arfaatun; Muhammad Muslimin (Madani: Jurnal Pengabdian Ilmiah, 2025)
Parenting seminars have become one of the most effective approaches to enhancing parents’ or guardians’ understanding and awareness of the importance of implementing positive parenting, especially for early childhood who are in a crucial phase of development at the Early Childhood Education (PAUD) and Kindergarten (TK) levels. These seminars function not only as a means of delivering information but are also designed as interactive forums where parents can receive education, gain practical skills, share experiences, and discuss the daily challenges of parenting. Positive parenting plays a significant role in shaping a child's character, building self-confidence, and supporting their physical, emotional, and social development. Parenting seminars also serve as a strategic platform for building collaboration between schools and parents in creating a safe, comfortable environment that maximally supports children’s development. Through an approach that emphasizes affection, effective communication, and the habituation of positive behavior, it is expected that parents can move away from authoritarian or permissive parenting styles, which are considered less suitable for supporting early childhood development. This article specifically discusses the implementation of a parenting seminar at PAUD and TK Muslimat Mazroatul Ulum 02, involving teachers, parents, and professional speakers in the field of child education and psychology. The discussion includes the seminar’s implementation methods, the content presented, participant engagement levels, the outcomes achieved, and the tangible impact on parenting practices in the family environment. Additionally, this article highlights the importance of sustaining parenting programs as regular activities that enhance parents' capacity to support their children's holistic development amid the dynamics of modern life.